Advanced Thermodynamics for Engineers - Winterbone, D. E.; Turan, Ali (Butterworth-Heinemann, 2015)
Advanced Thermodynamics for Engineers, Second Edition introduces the basic concepts of thermodynamics and applies them to a wide range of technologies. Authors Desmond Winterbone and Ali Turan also include a detailed study of combustion to show how the chemical energy in a fuel is converted into thermal energy and emissions; analyze fuel cells to give an understanding of the direct conversion of chemical energy to electrical power; and provide a study of property relationships to enable more sophisticated analyses to be made of irreversible thermodynamics, allowing for new ways of efficiently covering energy to power (e.g. solar energy, fuel cells). Worked examples are included in most of the chapters, followed by exercises with solutions. By developing thermodynamics from an explicitly equilibrium perspective and showing how all systems attempt to reach equilibrium (and the effects of these systems when they cannot), Advanced Thermodynamics for Engineers, Second Edition provides unparalleled insight into converting any form of energy into power. The theories and applications of this text are invaluable to students and professional engineers of all disciplines.